Pathogenesis of COVID-19 - A.E. Abaturov; E.A. Agafonova; E.L. Krivusha; A.A. Nikulina (Zaslavsky O.Yu., 2020)
Based on the literature, the article presents modern data on the main pathogenetic features of coronavirus infection associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which caused a pandemic, according to the World Health Organization definition, in 2019. The literature review details the processes of SARS-CoV-2 binding to a human cell receptor that express angiotensin-converting enzyme 2 (ACE2), as well as the internalization, replication of the virus, and the release of new virions from an infected cell, which affect target organs (lungs, digestive tract, heart, central nervous system and kidneys) and induce the development of local and systemic inflammatory responses. Existing methods of drug exposure that prevent human infection with SARS-CoV-2 are described. The main epidemiological moments of infection with SARS-CoV-2 were identified, indicating a predominant damage in the elderly and more often males due to the higher level of expression of angiotensin-converting enzyme 2, mostly in alveolocytes, than in females. The mechanisms of the development of the response of the innate and adaptive immune systems of a macroorganism to infection with SARS-CoV-2 are demonstrated. Therapeutic strategies are presented that are related to the effect of SARS-CoV-2 on various stages of vital activity: internalization - the use of soluble S-protein domains, antibodies against S-protein, single-chain variable fragment of antibodies to ACE2 or inhibition of glycosylation of cell receptors, blocking the interaction of SARS-CoV-2 S-protein with ACE2 protein and suppression of internalization of the virus by administration of chloroquine and hydroxychloroquine; replication - inhibition of a viral RNA-dependent RNA polymerase and the use of favipiravir, a non-nucleoside antiviral drug triazavirin, antiretroviral drugs (lopinavir in combination with ritonavir), nelfinavir, ribavirin, halidesivir, umifenovir, inhibitors of chymotrypsin-like protease (cinancerin, flavonoids) and papain-like protease. The above therapeutic methods in the near future will be aimed at preventing the development and treatment of both acute respiratory distress syndrome and conditions caused by damage to other targeted organs with COVID-19.